2017
DOI: 10.1002/tox.22492
|View full text |Cite
|
Sign up to set email alerts
|

Nickel oxide nanoparticles induce hepatocyte apoptosis via activating endoplasmic reticulum stress pathways in rats

Abstract: Nickel oxide nanoparticles (nano NiO) could induce hepatocyte apoptosis, while its potential mechanisms are unclear. This study aimed to explore the role of endoplasmic reticulum (ER) stress pathways in hepatocyte apoptosis induced by nano NiO. Male Wistar rats were administrated with nano NiO (0.015, 0.06, and 0.24 mg/kg b.w.) and micro NiO (0.24 mg/kg b.w.) by intratracheal instillation twice a week for 6 weeks. We measured the hepatocyte apoptosis levels by TdT-mediated dUTP nick-end labeling (TUNEL) staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Nano NiO causes cytotoxicity via excessive ROS generation, and induces cell apoptosis mediated by bax/bcl‐2 pathway in HepG2 cells . Our previous studies found that Nano NiO evoked hepatocyte apoptosis via endoplasmic reticulum stress pathway in rats . Additionally, Nano NiO exerts hepatic toxicity through oxidative stress and NF‐κB signaling pathway .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nano NiO causes cytotoxicity via excessive ROS generation, and induces cell apoptosis mediated by bax/bcl‐2 pathway in HepG2 cells . Our previous studies found that Nano NiO evoked hepatocyte apoptosis via endoplasmic reticulum stress pathway in rats . Additionally, Nano NiO exerts hepatic toxicity through oxidative stress and NF‐κB signaling pathway .…”
Section: Discussionmentioning
confidence: 95%
“…In addition, chronic liver damage promotes hepatic fibrosis in animal models . Our previous studies found that Nano NiO induced sub‐chronic liver lesion, which was associated with oxidative stress, hepatocyte apoptosis, and activation of Nuclear factor‐kappa B (NF‐κB) signaling pathway . Based on the above studies, we hypothesized that Nano NiO could lead to hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 97%
“…To quantify the relative mRNA expression of ERK1/2, P38 MAPK, MMP‐2, MMP‐9, TIMP‐1, and TIMP‐2, we performed RT‐qPCR with Bestar SYBR Green qPCR Mastermix kits (DBI Bioscience, Germany) in an IQ5 Multicolor Real‐Time PCR Detection System (Bio‐Rad, Hercules, California) according to the manufacturer's instructions. The steps of the program were described by our previous study . Beta‐actin (β‐actin) was used as the internal reference and we used the 2 −ΔΔct relative quantitation formula to quantify mRNA expression levels .…”
Section: Methodsmentioning
confidence: 99%
“…The steps of the program were described by our previous study. 1 Beta-actin (β-actin) was used as the internal reference and we used the 2 −ΔΔct relative quantitation formula to quantify mRNA expression levels. 31 The sequences and primers of all genes were designed and synthesized by Takara Biotechnology Co., Ltd. (Shanghai, China) and listed in Table 1.…”
Section: Measurement Of Hyp Contentsmentioning
confidence: 99%
See 1 more Smart Citation